The unbalanced indirect effects of task characteristics on performance in professional service outsourcing - Liu, Z.; Jayaraman, V.; Luo, Yadong (Elsevier, 2017)
© 2017 Elsevier B.V. As emerging markets have been playing more and more important roles in the global outsourcing markets, many companies from industrialized countries started to outsource various complex business processes oversea intending to take advantage of talented workforce at low cost. In this study, we focus on the challenging aspects and identify complex relationships that exist in the professional service outsourcing context from the service provider's perspective. Building on information processing theory, this paper aims to explain how task characteristics affect performance differently through a service provider's customer orientation and client integration. The unbalanced effects identified in this study influence the service provider's performance contradictorily and largely contribute to those unsatisfied results in professional service outsourcing. Using survey data from 192 Indian professional service providers, we find that both service provider's customer orientation and client integration are positively associated with its performance, while the impacts of two task characteristics (complexity and security) on customer orientation and client integration are in opposite direction. The unbalanced effects raise challenges in properly managing tasks to enhance performance. This study contributes to the much-needed efforts in the study of professional service outsourcing, a new and fast growing cross-border professional service activity. Managerial implications are also drawn from our study to practicing global clients and offshore service providers on how to successfully manage inter-organizational relations in outsourcing process to achieve expected benefits.